(7x+49)-2x=(2x+94)-2x

Simple and best practice solution for (7x+49)-2x=(2x+94)-2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (7x+49)-2x=(2x+94)-2x equation:



(7x+49)-2x=(2x+94)-2x
We move all terms to the left:
(7x+49)-2x-((2x+94)-2x)=0
We add all the numbers together, and all the variables
-2x+(7x+49)-((2x+94)-2x)=0
We get rid of parentheses
-2x+7x-((2x+94)-2x)+49=0
We calculate terms in parentheses: -((2x+94)-2x), so:
(2x+94)-2x
We add all the numbers together, and all the variables
-2x+(2x+94)
We get rid of parentheses
-2x+2x+94
We add all the numbers together, and all the variables
94
Back to the equation:
-(94)
We add all the numbers together, and all the variables
5x-45=0
We move all terms containing x to the left, all other terms to the right
5x=45
x=45/5
x=9

See similar equations:

| 68+60+x=180 | | 4x^2+5=8x | | y/4+10=-14 | | 2t-5=(-3) | | 10n-2n=2 | | 2/(x+3)+3/(x-4)=2x-2/x^2-x-12 | | -8=-2-3p | | (9x+72)-4x=(4x+112)-4x | | 2q-(-1)=3 | | y−(−1)=−5 | | 10x+7=41 | | 2/5g5=3/5 | | 3y-2=y+7 | | 10s-100=-197 | | 14-3t=5 | | 7y+5y+6y=5 | | 2p+9=3 | | 11=3d+5 | | 385/70=x/21 | | 40(r+2)+5r=26 | | x+37+x+79=15x-87 | | 9x-10=7x-10 | | 20=9,5+3y | | 127+22+x=180 | | 5(y-98)=-40 | | 70/385=21/x | | C=10x3.14 | | -c+7=1 | | 2w=6w-72 | | (2x+156)-4x=(4x+192)-4x | | 64=2^n+9 | | 6c+14=—5c+4+9c |

Equations solver categories